Assessing the role of LMS assessment tools in data-driven academic decisions: A case of the Faculty of Management Studies and Commerce in a selected state university in Sri Lanka - Sellahewa, N.N.; Manatunga, P.K.S. (University of Colombo, 2025)
Learning Management Systems have transformed higher education, offering tools that facilitate instruction, assessment, and academic decision-making. This study investigates how LMS assessment tools, particularly those integrated into Moodle, are associated with academic decision-making at the Faculty of Management Studies and Commerce in a state university in Sri Lanka. Specifically, it explores how the faculty utilizes LMS tools, assignments, quizzes, lessons, choice, workshop, survey and feedback and how their perceived convenience, accessibility, simplicity, and benefits influence academic decisions such as curriculum development, student evaluation, and instructional improvement. The research employes a quantitative approach grounded in the Technology Acceptance Model, based on responses from 150 early-career academics. The study revealed that assignments, quizzes, and lessons were the most used LMS tools, while workshops and surveys were less utilized. Among the respondents, Temporary Assistant Lecturers (36%) and Probationary Lecturers (29.3%) represented the largest groups. Participants reported strong positive perceptions of the LMS assessment tools in terms of convenience, accessibility, simplicity, and benefits (mean > 4.4, SD < 1.00). Correlation analysis showed significant relationships with academic decision-making, notably simplicity (r = 0.770) and convenience (r = 0.718). The regression model was significant (F = 44.364, p < 0.001), explaining 73.8% of the variance (Adjusted R² = 0.738), with all predictors significant (p < 0.01). No multicollinearity issues were detected (VIF < 2.7). The findings underscore the need for targeted interventions to maximize the effectiveness of LMS tools in academic decision-making. Universities should implement regular training programmes to improve faculty proficiency in utilizing the full range of LMS features beyond commonly used tools like quizzes and assignments. Additionally, LMS platforms must be designed with a focus on simplicity and mobile responsiveness to encourage broader adoption and ease of use. At the policy level, academic administrators are encouraged to integrate LMS-generated data into routine decision-making processes, particularly for curriculum development and instructional improvements.
Keywords: Academic; Decision-making; Assessment tools; LMS; Moodle